2023
DOI: 10.1021/jacs.2c11451
|View full text |Cite
|
Sign up to set email alerts
|

Diversifying Amino Acids and Peptides via Deaminative Reductive Cross-Couplings Leveraging High-Throughput Experimentation

Abstract: A deaminative reductive coupling of amino acid pyridinium salts with aryl bromides has been developed to enable efficient synthesis of noncanonical amino acids and diversification of peptides. This method transforms natural, commercially available lysine, ornithine, diaminobutanoic acid, and diaminopropanoic acid to aryl alanines and homologated derivatives with varying chain lengths. Attractive features include ability to transverse scales, tolerance of pharma-relevant (hetero)aryls and biorthogonal functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 63 publications
(30 reference statements)
0
28
0
Order By: Relevance
“…Producing carbon–carbon bonds from readily available feedstocks is particularly impactful. The C­(sp 3 )–C­(sp 2 ) substructure is often synthesized from an organometallic reagent and an alkyl or aryl (pseudo)­halide via cross-coupling with palladium, nickel, copper, iron, cobalt, or other metal catalysts. Recently, nickel catalysis has found complementary utility in reductive C­(sp 3 )–C­(sp 2 ) couplings. …”
mentioning
confidence: 99%
“…Producing carbon–carbon bonds from readily available feedstocks is particularly impactful. The C­(sp 3 )–C­(sp 2 ) substructure is often synthesized from an organometallic reagent and an alkyl or aryl (pseudo)­halide via cross-coupling with palladium, nickel, copper, iron, cobalt, or other metal catalysts. Recently, nickel catalysis has found complementary utility in reductive C­(sp 3 )–C­(sp 2 ) couplings. …”
mentioning
confidence: 99%
“…Openy et al showcased the first example of utilizing a side chain Katritzky salt for on-resin peptide LSF, accessing diverse ncAAs via a photochemical Giese reaction using commercially available Michael acceptors . With line of sight to readily transform abundant canonical AA feedstocks into unique ncAAs, an academic–industrial collaboration between Merck and the Watson group at the University of Delaware recently reported a cross-electrophile coupling between lysine-derived Katritzky salts and aryl halides to access aryl alanines and homologated derivatives (Figure D) . Through this work, facile access to LSF substrates was achieved, ultimately providing diverse, boutique side chain functionality on fully elaborated peptidic structures.…”
Section: Advances In Peptide Medicinal Chemistry: Leveraging Late-sta...mentioning
confidence: 99%
“…The Watson method enables amines to be converted into active electrophiles and then cross-coupled with a variety of coupling partners . Rich collaborations have already developed between her group and researchers from the pharmaceutical industry to leverage this exciting new advance. …”
mentioning
confidence: 99%
“…Further, through detailed mechanistic studies, the Watson Group has shown that the transformation proceeds via a radical intermediate for Katritzky salts, which is likely generated by single electron transfer from the nickel catalyst to the pyridinium salt . In collaboration with researchers from Merck, the Watson Group has shown how the method, when applied to amino acid side chains, can be used to create structures with noncanonical amino acids …”
mentioning
confidence: 99%
See 1 more Smart Citation